Bacterial Cellulose Production in Thai Red Tea Fermentation: Role of Sucrose-Based Sugar Combinations as Carbon Sources - Agustina, Wawan; Boontawan, Apichat (Trends in Sciences, 2025)
Bacterial cellulose (BC) is a versatile biopolymer produced via microbial fermentation, valued for its purity, strength, and biocompatibility. In this study, BC was synthesized using Thai red tea as the fermentation medium, combined with various carbon source combinations: Control (RTC-C), sucrose-dextrose (RTC-SD), sucrose-glucose (RTC-SGlu), sucrose-fructose (RTC-SF), and sucrose-glycerol (RTC-SGly). Fermentation was carried out for 15 days at 30 °C using a tea solution (1% w/v), total sugar content of 10% (w/v), and 10% (v/v) kombucha culture. The resulting BC was evaluated for yield, morphology, structure, and thermal/mechanical properties using SEM, FTIR, XRD, and TGA analysis. Carbon source combinations significantly influenced BC production, with wet and dry yields ranging from 74.53 g/L and 0.66 g/L (RTC-SGly) to 259.54 g/L and 2.59 g/L (RTC-SGlu), respectively. The sucrose-glucose combination yielded the highest productivity. SEM revealed a uniform nanofiber network with fiber diameters ranging from 29.70 ± 5.17 nm to 40.39 ± 8.65 nm. FTIR and XRD confirmed the formation of cellulose type I, with crystallinity indexes ranging from 84.74% (RTC-SGly) to 88.35% (RTC-SF). Thermal and mechanical properties were comparable across all samples. These findings demonstrate that specific carbon source combinations, particularly sucrose-glucose and sucrose-dextrose, can significantly enhance BC yield without compromising its structural integrity, highlighting their potential for industrial-scale applications. HIGHLIGHTS Thai red tea fermentation serves as an effective substrate for bacterial cellulose production. Fermentation medium composition, especially carbon source combinations, plays a key role in influencing BC yield and characteristics. Sucrose combined with glucose or dextrose significantly improves BC productivity over sucrose alone. Structural, thermal, and mechanical properties remain stable across treatments, despite enhanced yield. GRAPHICAL ABSTRACT